Les agglomérations de la province de Lyonnaise Troisième (Bretagne et Pays de la Loire) : entre abandon, perduration et nouvelles créations (iiie-vie s. apr. J.-C.) - Martial Monteil (Gallia)
This paper focuses on the province of Lugdunensis Tertia as it can be restituted at the end of 4th c. AD, though excluding the civitas Turonensis and considering only the eight civitates corresponding to Bretagne and Pays de la Loire. The question of the future of the urban network during Late Antiquity is discussed here, identifying the gaps regarding the documentation. Despite these gaps, it is possible to highlight the diversity of the towns trajectories, which range between total abandonment, possible, probable or certain perduration, and restructuration. Along the 5th-6th c., we observe an important retraction of the urban network, which is however balanced by the creation of new agglomerations whose existence appears in some textual and numismatic sources.